Evidence of recent and delayed complaint at the trial for rape: comparative jurisdiction - Mohamad Yunus, Mohamad Ismail (Global Press, 2014)
The evidential rules as applied to sexual assault cases have been and remain a cause for some concern. This research paper will focus on the evidential law relating to the admissibility of recent complaint rule.